Preliminary screening for microsatellite instability and loss of heterozygosity in the deleted in colorectal cancer (dcc) gene among Filipino patients with colorectal adenocarcinoma - Arnante, Michael Ernesto S. (Animo Repository, 2014)
Objective. This study aimed to detect the presence of microsatellite instability (MSI) and loss of heterozygosity (LOH) of the Deleted in Colorectal Cancer (DCC) gene in normal and tumor tissues of Filipino colorectal cancer patients and examine its correlation with age, gender, tumor grade, tumor stage and site of lesion. Methods. Paired frozen normal and tumor tissues from thirty-nine (39) patients with colorectal adenocarcinoma were used in this study. Genomic DNA was extracted and amplified by polymerase chain reaction (PCR). Single strand conformation polymorphism - polyacrylamide gel electrophoresis (SSCP -PAGE) was used to determine MSI and restriction fragment length polymorphism (RFLP) was used to study LOH. Results. Based on our data, out of the 39 patients, 10 showed LOH of the DCC gene using the LOH markers VNTR, M2 and M3, while no MSI was detected in the samples using the MSI markers BAT25 and BAT26. Correlation with clinicopathological characteristics showed that there is significance for the site of lesion. The LOH has correlation with tumor samples from the colon but not with those from the rectum. Conclusion. Preliminary screening for MSI and LOH of the DCC gene shows that occurrence of colorectal cancer among Filipino patients can be correlated with LOH of the DCC gene but not with MSI. This may be the first study to examine the correlation or lack thereof of MSI and LOH of the DCC gene with colorectal cancer in a Filipino sample population.